Riser-seabed interaction in the touchdown zone using fibre optic sensing in a geotechnical centrifuge - C., O’Beirne; Christophe, Gaudin; Phil, Watson; Mark, Randolph; Fauzan, Sahdi (2022)
Fatigue damage of Steel Catenary Risers (SCRs) is typically greatest within the touchdown zone (TDZ), where cyclic interaction of the riser with the seabed results in complex changes of soil properties and potential changes in riser curvature, especially if a trench forms. This complex phenomenon has prompted researchers to pursue improved understanding of SCR behaviour in the TDZ, to enhance design life assessment and overall design. Past studies have shown that modelling a section of the riser around the TDZ can satisfactorily capture touchdown behaviour. However, the use of conventional strain gauges may result in unwanted stiffening of the model, while also limiting the number of data points at which strain is measured. This paper presents centrifuge tests performed using a SCR model instrumented with a novel fibre optic sensing system. The system comprises three Fibre Braggs Grating fibre strands along the SCR model, separated circumferentially by 120º in cross section, with each strand measuring over 350 points of strain. Realistic sea states were scaled and translated to the cut-off point on the riser above an elastic (dummy) seabed, with surge, heave and sway motions simultaneously applied using three degrees of actuation. The riser-seabed interaction along the TDZ was successfully captured, with experimental results validated against finite element analyses. Following the success of this campaign, the model is now being used to explore response on clay seabed samples, which will further advance understanding of SCR behaviour at the TDZ.